Hydration, mechanical properties and microstructure of lime-pozzolana pastes by recycling waste sludge ash under marine environment. (10th August 2021) - Zhou, Yi-fan; Lu, Jian-xin; Li, Jiang-shan; Cheeseman, Chris; Poon, Chi Sun
Abstract: To date, the effects of seawater have seldomly been investigated on the hydration of lime-pozzolan system. Also, to explore the feasibility of using lime-incinerated sewage sludge ash (ISSA)/coal fly ash (FA) as a binder for the stabilisation/solidification (S/S) of marine sediments, hydration kinetics, mechanical strength development and microstructural characteristics of lime-ISSA/FA binder hydrated using seawater are discussed in this study. The results showed that seawater initially accelerates the hydration of lime-ISSA but not the lime-FA system. The early-age and long-term compressive strength of both lime-ISSA and lime-FA system with seawater mixing was effectively increased compared to hydration using normal freshwater. Calcium phosphate hydrate and Friedel's salt was formed in the lime-ISSA system and this contributes to forming a dense microstructure. Pastes hydrated with seawater also exhibited fine porosity compared to samples hydrated using freshwater and this also contributes to improved mechanical properties. Such a type of green binder without using Portland cement would be beneficial in waste materials (i.e. ISSA and FA) upcycling and this work was expected to guide the future works on employing the lime-ISSA/FA binder on S/S of marine sediments. Highlights: Recycling high volume of ISSA in lime-pozzolan system enables sustainable management of waste materials. The impact of seawater on the lime-pozzolan (ISSA and FA) pastes is investigated and compared. Hydration of lime-ISSA system using seawater is advantageous for strength development. Seawater mixing leads to formation of Friedel's salt, dense hydrating matrix and decreased porosity.